2022
DOI: 10.3389/fcimb.2022.927131
|View full text |Cite
|
Sign up to set email alerts
|

Role of Immunity and Vaginal Microbiome in Clearance and Persistence of Human Papillomavirus Infection

Abstract: Cervical cancer disproportionately affects women of reproductive age, with 80% of cases occurring in low- and middle-income countries. Persistent infection with high-risk human papillomavirus (HPV) genotypes has been described as the most common non-systemic biological risk factor for the development of cervical cancer. The mucosal immune system plays a significant role in controlling HPV infection by acting as the first line of host defense at the mucosal surface. However, the virus can evade host immunity us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 117 publications
2
22
0
Order By: Relevance
“…The main factor in cervical carcinogenesis is HPV infection, and the microbiome that accompanies HPV infection is one of the most important co-factors in cell transformation. Host defense mechanisms, including immune mediators in the female genital tract microenvironment, play a role in the clearance and persistence of HPV and the risk of developing cervical cancer 26. The composition of the microbiota is influenced by numerous factors, with ethnicity being the main intrinsic factor associated with the microbiome composition 10.…”
Section: Discussionmentioning
confidence: 99%
“…The main factor in cervical carcinogenesis is HPV infection, and the microbiome that accompanies HPV infection is one of the most important co-factors in cell transformation. Host defense mechanisms, including immune mediators in the female genital tract microenvironment, play a role in the clearance and persistence of HPV and the risk of developing cervical cancer 26. The composition of the microbiota is influenced by numerous factors, with ethnicity being the main intrinsic factor associated with the microbiome composition 10.…”
Section: Discussionmentioning
confidence: 99%
“…Both HPV16 and 18 can evade innate immune responses by suppressing the synthesis of interferons. Furthermore, HPV can avoid adaptive immune responses by modulating the level of T regulatory cells, leading to immune suppression 8 . In conclusion, the pathogenesis of HPV‐induced cervical cancer is a multifaceted and intricate process that involves viral DNA integration, inactivation of tumor suppressor proteins, deregulation of the cell cycle, and subsequent genetic and epigenetic modifications.…”
Section: Figurementioning
confidence: 99%
“…Although most HPV infectious cases can be cleared in the first 2 years ( 2 ), the factors that promote HPV persistence and trigger carcinogenic pathways are not fully understood. In recent years, vaginal microecology has become a research hotspot for various gynecological diseases, and a variety of vaginal microbiota and related inflammation has been found to be potential drivers of HPV infection and disease severity ( 3 ). Previous studies have revealed that bacterial vaginosis (BV) and decreased Lactobacilli are associated with an increased risk of HPV infection ( 4 , 5 ), while the relationships between Trichomoniasis , vulvovaginal Candidiasis (VVC), and other vaginal microdysbiosis and HPV infection are controversial ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%